Pesticides and herbicides. (19th August 2020) - Choudri, B. S.; Charabi, Yassine; Al‐Nasiri, Noura; Al‐Awadhi, Talal
Abstract: This paper highlights a review of scientific papers published in the year 2019 regarding pesticides and herbicides. The scientific review presented in this paper includes the presence and occurrence of pesticides and herbicides in the environment. The entire review divided into different sections, which are grouped into four main sections. Each of these sections provides studies conducted on toxicology, ecological risk assessment, strategies of treatment, policies, modeling, and guidelines regarding pesticides and herbicides management. Practitioners points: This paper highlights the review of scientific literature published in the year 2019. The review includes the presence and occurrence of pesticides and herbicides in the environment. The review focuses on toxicology, ecological risk assessment, strategies of treatment, policies, modelling and guidelines regarding pesticides and herbicides management. The literature review covers selected papers relevant to the topic.